The Defense of Inge Indai Language Within The Family Context of Lambitu Community - Rahmatia Ardila; Fathur Rokhman; Hari Bakti Mardikantoro (International Conference on Science, Education, and Technology, 2021)
The spoken language variety of Lambitu community, Sambori village, represents the bilinguality and multilinguality of the community. This research aims to analyze the defense realization of Inge Ndai language within the family context of Lambitu community. This qualitative research collected the data with listening method. Then, the researcher continued it with non-participant observer. The researcher recorded and noted the conversation. The data analysis used match method. The results showed that the language defense in family of Lambitu community, Sambori village were: (1) single Inge Ndai language, (2) code switching, and (3) code mixing